Digitoxigenin presents an effective and selective antileishmanial action against Leishmania infantum and is a potential therapeutic agent for visceral leishmaniasis - Freitas, Camila S.; Oliveira-da-Silva, João A.; Lage, Daniela P.; Costa, Rafaella R.; Mendonça, Débora V.C.; Martins, Vívian T.; Reis, Thiago A.R.; Antinarelli, Luciana M.R.; Machado, Amanda S.; Tavares, Grasiele S.V.; Ramos, Fernanda F.; Coelho, Vinicio T.S.; et al. (Parasitology Research, 2020)
Treatment for visceral leishmaniasis (VL) is hampered mainly by drug toxicity, their high cost, and parasite resistance. Drug development is a long and pricey process, and therefore, drug repositioning may be an alternative worth pursuing. Cardenolides are used to treat cardiac diseases, especially those obtained from Digitalis species. In the present study, cardenolide digitoxigenin (DIGI) obtained from a methanolic extract of Digitalis lanata leaves was tested for its antileishmanial activity against Leishmania infantum species. Results showed that 50% Leishmania and murine macrophage inhibitory concentrations (IC50 and CC50, respectively) were of 6.9 ± 1.5 and 295.3 ± 14.5 μg/mL, respectively. With amphotericin B (AmpB) deoxycholate, used as a control drug, values of 0.13 ± 0.02 and 0.79 ± 0.12 μg/mL, respectively, were observed. Selectivity index (SI) values were of 42.8 and 6.1 for DIGI and AmpB, respectively. Preliminary studies suggested that the mechanism of action for DIGI is to cause alterations in the mitochondrial membrane potential, to increase the levels of reactive oxygen species and induce accumulation of lipid bodies in the parasites. DIGI was incorporated into Pluronic® F127-based polymeric micelles, and the formula (DIGI/Mic) was used to treat L. infantum–infected mice. Miltefosine was used as a control drug. Results showed that animals treated with either miltefosine, DIGI, or DIGI/Mic presented significant reductions in the parasite load in their spleens, livers, bone marrows, and draining lymph nodes, as well as the development of a specific Th1-type response, when compared with the controls. Results obtained 1 day after treatment were corroborated with data corresponding to 15 days after therapy. Importantly, treatment with DIGI/Mic induced better parasitological and immunological responses when compared with miltefosine- and DIGI-treated mice. In conclusion, DIGI/Mic has the potential to be used as a therapeutic agent to protect against L. infantum infection, and it is therefore worth of consideration in future studies addressing VL treatment.
CRIS-Team Scopus Importer:2020-11-20
Keywords: Amphotericin B deoxycholate; Digitoxigenin; Drug repositioning; Miltefosine; Treatment; Visceral leishmaniasis